International Economics - Pugel, Thomas (Pearson, 2024)
The text is informed by current events and includes the latest in applied international research. Like earlier editions, Pugel also places international economics events within a historical framework. The overall treatment continues to be intuitive rather than mathematical and is strongly oriented towards policy.